Interaction between Tat and Drugs of Abuse during HIV-1 Infection and Central Nervous System Disease - Maubert, Monique E.; Pirrone, Vanessa; Rivera, Nina T.; Wigdahl, Brian; Nonnemacher, Michael R. (Frontiers in Microbiology, 2016)
In many individuals, drug abuse is intimately linked with HIV-1 infection. In addition to being associated with one-third of all HIV-1 infections in the United States, drug abuse also plays a role in disease progression and severity in HIV-1-infected patients, including adverse effects on the central nervous system (CNS). Specific systems within the brain are known to be damaged in HIV-1-infected individuals and this damage is similar to that observed in drug abuse. Even in the era of anti-retroviral therapy (ART), CNS pathogenesis occurs with HIV-1 infection, with a broad range of cognitive impairment observed, collectively referred to as HIV-1-associated neurocognitive disorders (HAND). A number of HIV-1 proteins (Tat, gp120, Nef, Vpr) have been implicated in the etiology of pathogenesis and disease as a result of the biologic activity of the extracellular form of each of the proteins in a number of tissues, including the CNS, even in ART-suppressed patients. In this review, we have made Tat the center of attention for a number of reasons. First, it has been shown to be synthesized and secreted by HIV-1-infected cells in the CNS, despite the most effective suppression therapies available to date. Second, Tat has been shown to alter the functions of several host factors, disrupting the molecular and biochemical balance of numerous pathways contributing to cellular toxicity, dysfunction, and death. In addition, the advantages and disadvantages of ART suppression with regard to controlling the genesis and progression of neurocognitive impairment are currently under debate in the field and are yet to be fully determined. In this review, we discuss the individual and concerted contributions of HIV-1 Tat, drug abuse, and ART with respect to damage in the CNS, and how these factors contribute to the development of HAND in HIV-1-infected patients.